Pamidronate-encapsulated electrospun polycaprolactone as a potential bone regenerative scaffold. (March 2019) - Remya, KR; Chandran, Sunitha; John, Annie; Ramesh, P
This study explores the potential of electrospun polycaprolactone scaffolds for the controlled delivery of pamidronate disodium pentahydrate, an amino-bisphosphonate drug used for the treatment of osteoporosis. Major drawbacks associated with oral bisphosphonate therapy are its poor bioavailability and gastrointestinal side-effects. Herein, we used polycaprolactone, a well-known Food and Drug Administration–approved biomaterial, as the delivering vehicle for pamidronate disodium pentahydrate. Scaffolds based on polycaprolactone with three different formulations (1, 3, and 5 wt%) of pamidronate disodium pentahydrate were fabricated by electrospinning, and a comparative study was carried out to evaluate the effect of pamidronate disodium pentahydrate on physico-mechanical and biological properties of polycaprolactone. The observations from Fourier-transform infrared spectra and thermogravimetric analysis confirmed the successful incorporation of pamidronate disodium pentahydrate into polycaprolactone scaffolds. The study also revealed that pamidronate disodium pentahydrate–loaded scaffolds exhibited improved hydrophilicity as well as superior mechanical properties as depicted by the contact angle measurements and mechanical property evaluation. In vitro drug release studies of pamidronate disodium pentahydrate–loaded scaffolds in phosphate buffer saline at 37°C showed that all the scaffolds exhibited controlled release of pamidronate disodium pentahydrate. In vitro degradation studies further revealed that pamidronate disodium pentahydrate incorporated polycaprolactone scaffolds degraded faster as depicted by the fiber rupture and drop in mechanical properties. In vitro cell culture studies using human osteosarcoma cell lines demonstrated that pamidronate disodium pentahydrate–loaded polycaprolactone scaffolds were cytocompatible. The human osteosarcoma cells had favorable interaction with the scaffolds, and the viability of adhered cells was depicted by the fluorescein diacetate/propidium iodide staining. MTT assay further revealed enhanced cell viability on PCL/PDS3 scaffolds. Our findings bespeak that the pamidronate disodium pentahydrate–encapsulated electrospun polycaprolactone scaffolds have the potential to serve as a promising drug delivery vehicle for osteoporotic bone defect repair.